Sialidase Activity in the Cervicovaginal Fluid Is Associated With Changes in Bacterial Components of Lactobacillus-Deprived Microbiota - Ferreira, Carolina Sanitá Tafner; Marconi, Camila; Parada, Cristina M. G. L.; Ravel, Jacques; Silva, Marcia Guimaraes da (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Sialidase activity in the cervicovaginal fluid (CVF) is associated with microscopic findings of bacterial vaginosis (BV). Sequencing of bacterial 16S rRNA gene in vaginal samples has revealed that the majority of microscopic BV cases fit into vaginal community-state type IV (CST IV), which was recently named “molecular-BV.” Bacterial vaginosis-associated bacterial species, such as Gardnerella spp., may act as sources of CVF sialidases. These hydrolases lead to impairment of local immunity and enable bacterial adhesion to epithelial and biofilm formation. However, the impact of CVL sialidase on microbiota components and diversity remains unknown. Objective To assess if CVF sialidase activity is associated with changes in bacterial components of CST IV. Methods One hundred forty women were cross-sectionally enrolled. The presence of molecular-BV (CST IV) was assessed by V3–V4 16S rRNA sequencing (Illumina). Fluorometric assays were performed using 2-(4-methylumbelliferyl)-α-D-N-acetylneuraminic acid (MUAN) for measuring sialidase activity in CVF samples. Linear discriminant analysis effect size (LEfSe) was performed to identify the differently enriched bacterial taxa in molecular-BV according to the status of CVF sialidase activity. Results Forty-four participants (31.4%) had molecular-BV, of which 30 (68.2%) had sialidase activity at detectable levels. A total of 24 bacterial taxa were enriched in the presence of sialidase activity, while just two taxa were enriched in sialidase-negative samples. Conclusion Sialidase activity in molecular-BV is associated with changes in bacterial components of the local microbiome. This association should be further investigated, since it may result in diminished local defenses against pathogens.